2013
DOI: 10.1159/000356499
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Maternal Neutrophil Gelatinase-Associated Lipocalin in Women with Severe Early-Onset Preeclampsia

Abstract: Introduction: The association between maternal plasma levels of neutrophil gelatinase-associated lipocalin (NGAL) and maternal complications in women admitted with severe early-onset preeclampsia was evaluated. Material and Methods: Plasma levels of NGAL were measured at admission in patients with severe early-onset (presenting before 34 weeks) preeclampsia. The maternal outcome of women with elevated plasma levels was compared with those with normal levels. Maternal complications included eclampsia, HELLP syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…In our study, serum NGAL levels had a range of 15.26 -26.03 ng/mL with a homogenous distribution. These mean values were far below the values reported by Scazzochio et al (9). We did not have any maternal complications such as HELLP or eclampsia.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In our study, serum NGAL levels had a range of 15.26 -26.03 ng/mL with a homogenous distribution. These mean values were far below the values reported by Scazzochio et al (9). We did not have any maternal complications such as HELLP or eclampsia.…”
Section: Discussioncontrasting
confidence: 63%
“…Stepan et al (19) have shown that serum NGAL was significantly higher in women with EOPE compared to uncompli-cated pregnancy. Scazzochio et al (9) have shown that serum NGAL was significantly higher in women with early-onset severe preeclampsia compared to uncomplicated pregnancy. Maternal complications such as HELLP were more common with serum NGAL levels above 100 ng/mL, although neonatal complications were comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of publications showing the utility of NGAL for diagnosing and assessing the severity of preeclampsia. 17 23 The increase in NGAL due to preeclampsia is attributed to the presence of endothelium dysfunction and systemic inflammation. 24 The range of serum NGAL reported in these previous studies is very wide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that circulating levels of NGAL correlate with the presence and severity of preeclampsia [26]. It might be involved in the pathophysiology of preeclampsia and could be a marker for this syndrome.…”
Section: Commentsmentioning
confidence: 99%